Efektifitas Penggunaan Google Classroom Sebagai Media Pembelajaran Mata Pelajaran Sistem Pengendali Elektronik Pada Masa Pandemi Covid-19 di SMKN Lengkong Kabupaten Nganjuk - Septian Iswanjaya (PINUS: Jurnal Penelitian Inovasi Pembelajaran, 2024)
Abstract The COVID-19 pandemic makes a change to the learning system. Online learning is a learning system that use today. Google Classroom is an application made by Google LLC. which is used for online learning. The purpose of this study is to determine the effectiveness of using Google Classroom as a means of online learning media for the Electronic Control Systems subject during the COVID-19 pandemic. The method used was a questionnaire through Google Form for 33 students of the Electronic Control System subject. The results of this research indicate that students are hesitant about the application of Google Classroom for online learning media in the subject of Electronic Control Systems at SMK Negeri Lengkong Kab. Nganjuk with an average percentage value 70.18%. For ease of application, students are still in doubt that Google Classroom is used as an online learning media, with a percentage value of 77.09%. Keywords: COVID-19, Google Classroom, Electronics System Control